Gross motor skills performance in children with dyslexia: a comparisonbetween younger and older children - Nur Sakinah Baharudin; Dzalani Harun; Masne Kadar; Hanif Farhan Mohd Rasdi; Suhaili Ibrahim (Penerbit Universiti Kebangsaan Malaysia, 2019)
Children with dyslexia are commonly associated with gross motor difficulties. However, this non-literacy symptom is often overlooked as an important feature of dyslexia. Therefore, the aims of this study were to determine gross motor skills status among children with dyslexia and to compare the gross motor skills between younger and older children. A cross-sectional study was conducted on children with dyslexia from government schools and Dyslexia Association Malaysia. The participants were divided into two groups, namely younger (4 to 10 years) and older children (11 to 17 years old), and were recruited randomly. The gross motor skills were measured using the Bruininks-Oseretsky Test of Motor Proficiency, Second Edition (BOT-2) (subtests: Body Coordination, and, Strength and Agility) and the Movement Assessment Battery for Children, Second Edition (MABC-2) (subtest: Aiming and Catching). Standard scores and percentile rankings were used for statistical analysis. A total of 82 children with dyslexia were recruited for this study, consisted of younger (n = 57) and older groups of children (n = 25). The younger children were found to have a significantly lower performance in gross motor skills in Body Coordination (Mdn = 48, IQR = 26-63), compared to the older children, (Mdn = 54, IQR = 30-77), with a small effect size (r = -.25). There were no significant different for other findings. The older children were found to demonstrate the highest level of gross motor skills. This study may suggest the need for an early intervention program for young age children with dyslexia. Future studies that assess gross motor skills using longitudinal design are recommended to investigate the changes in gross motor performance over time.